On the statistical theory of visco-elastic properties of electrolyte solutions - Odinaev, S.; Dodarbekov, A. (Condensed Matter Physics, 2001)
Based on the generalized kinetic equation for single and pair correlation
distribution functions, analytical expressions for dynamic coefficients of
shear and bulk viscosity and corresponding elastic modulus are obtained.
The frequency dispersion of these coefficients and elastic modulus are
caused mainly by translational and structural relaxation processes. The
asymptotic behaviour of these expressions at low and high frequency is
investigated. Отримано аналітичні вирази для динамічних коефіцієнтів зсувної
та об’ємної в’язкості та відповідних модулів пружності на основі
розв’язку узагальненого кінетичного рівняння для одно- та двочастинкових кореляційних функцій. Частотна дисперсія цих коефіцієнтів і модулів пружності зумовлена в основному трансляційними та
структурними релаксаційними процесами. Встановлена асимптотична низько- та високочастотна поведінка отриманих виразів.